Pork-Barrel versus Irrelevance effects in portuguese public spending - Mourão, Paulo (2013)
Pork-barrel effects are discussed using a specific program of Portuguese investment expenditures (PIDDAC) that has been observed since 1997. Our framework adds new insight to this important branch of Economics literature. First, our analysis is the first to be based on Sequential Dictators Games, which are more appropriate for studying the strategies of the agents involved in pork-barrel practices. Second, we examine the role of ‘irrelevance effects’, which limit or offset the pork-barrel effect even if the recipient municipality and the Portuguese Government are ruled by the same political wing. Our empirical estimations confirm that the Portuguese government tends to increase PIDDAC transfers to the municipalities that are being ruled by the same political wing. Municipalities with fewer residents or fewer parishes tend to suffer the most significant irrelevance effects. PIDDAC transfers to all municipalities were found to be more generous during election years.